The concert for viola and orchestra by Hennady Liashenko as a reflection of his world outlook - Komlikova Anastasiіa (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. Hennady Liashenko is one of the most original Ukrainian composers of our days. His compositions have unique structural and linguistic-style features. In Concerto for viola and orchestra the author meditates on different philosophic questions which reflect his personal world outlook. His principles of thinking and material development are based on the intimate soul experience. Concerto for viola – important work of Liashenko creativity – do not study and analyze in music science before. This research helps to understand better the conceptual features of concerto and it`s connection with individual positions. Main objective of the study is music material of Concerto and it`s parallel to composer`s world outlook. Methodology consists in analyzing the music form, harmony, orchestration, thematism and the specifics of the genre`s interpretation. How the study was done. The individual traits of H. Liashenko’s composer’s writing were detected by means of the detailed analyze of score. The search of connection with the personal characters of composer is based on the observation. Results and conclusions. The particular attention is paid to the principles of interaction of the solo instrument with the orchestra, the construction of the viola`s party which the issue is considered both from the standpoint of material`s development, and from the standpoint of virtuosity and the application of various techniques of the playing. The significant influence of the intonational (sometimes harmonic) sphere and the rhythmic organization on the general dramaturgy of the work (intensification of dissonance – relaxation, free, like improvisational rhythmic constructions – turning) is revealed, which is based on the comparison of opposite images. The main means of realizing the author`s design that has a philosophical basis (the composer operates with the concepts of motion and rest, uses the rhythmic randomization etc.) is variability and confrontation lyric and active positions. The interaction of two images was finished by the victory of idealistic sphere. This dramaturgic way shows the importance of inside life for person. Practical significance. The research complements the science knowledge about the creativity and individual of Hennady Liashenko. Also it will be useful for performers of Viola`s concerto and for next works about creative heritage of composer.